Management of Stholya (Obesity) by Panchakarma (AYUSHDHARA, 2024)
The changes in the lifestyle have made the modern man sedentary and inactive. Moreover, during the course of time, the dietary habits have also changed a lot towards junk foods and drinks. Due to these factors the prevalence of obesity is growing worldwide, resulting in multi systemic disorders like diabetes, hypertension, cardiac abnormalities etc. For the treatment of obesity, modern medicine emphasis upon calorie restriction in the diet, exercises and appetite suppressant drugs, but these drugs have adverse actions on other systems and may produce symptoms like dryness of mouth, constipation, migraine headache, menstrual disorders etc. In Ayurveda, obesity has been described as Santarpanokta vikara under the heading Stholya. For the treatment in Ayurveda, Langhana (fasting), Vyayama (regular exercise) and Shodhana (purification measures) have been advised by our Acharyas. At the same time, these modalities are effective, without side effects, economic and easily available. So, Ayurveda can provide a better choice of treatment in Stholya through Panchakarma modalities. A 23 years old female patient came to Panchakarma O.P.D. was weighing 103kg with height 161cm; BMI was 39.70kg/m2 and according to the guidelines of NHI it falls under the class II obese category. She was treated with Aama pachana, Rukshana karma i.e., Udwartana, Snehana (Abhyantra and Bahya), Swedana, Virechana and Basti along with oral medicines, dietary regimes and life style modification. She lost about 23 kg of weight, which was 80 g and BMI was 30.90kg/m2 after 5 months of Panchakarma and oral treatment without any complications.